Students’ Mathematical Connection Ability and Self Regulated Learning on MiC Learning with Recitation and Peer Assessment Based on Semarang Culture - Millaty, Vita Nur; Kartono, Kartono; Karomah Dwidayati, Nur (Unnes Journal of Mathematics Education Research, 2019)
This research was aimed (1) to know the effectiveness of MiC learning with recitation and peer assessment based on Semarang Culture to students’ mathematical connection ability and (2) to analyze students’ mathematical connection ability and self regulated learning. This study was a mixed method research with a sequential explanatory design. The population was 7th grade students of SMP N 32 Semarang academic year 2017/2018. The subjects was selected based on the students’ initial matehamtical ability which is categorized as upper, middle and lower group students. Data was collecting by questionnaire, observation, test, and interview. The result showed that (1) MiC learning with recitation and peer assessment based on Semarang Culture is effective on students’ mathematical connection ability, (2) students in the upper group category can connect between topics in mathematics, connect mathematical concepts with other diciplines, connect mathematics with daily life well and have a high level of self regulated learning, students in the middle group category can connect mathematical concepts with other diciplines and connect mathematics with daily life well and have a moderate level of self regulated learning, and for students in lower group category can connect mathematical concepts to other diciplines well and have a low level of self regulated learning.